Morphological changes in the myocardium of rats with chronic alcohol intoxication after treatment with new GABAand glutamic acid derivatives - A. A. Nesterova; I. I. Prokofiev; V. N. Perfilova; O. Yu. Evsyukov; M. V. Kustova; I. N. Tyurenkov (Бюллетень сибирской медицины)
Aim. To study pathohistological changes in the myocardium of rats with chronic alcohol intoxication (CAI) after treatment with a new glutamic acid derivative glufimet (compound RSPU-238) and a new gamma-aminobutyric acid (GABA) derivative (compound RSPU-260).Materials and methods. Experiments were performed on female Wistar rats aged 10 months. The rats were divided into the following groups: group 1 – intact females; group 2 – a control group which included animals after CAI simulated by replacing drinking water with 10% ethanol solution for 24 weeks; groups 3 and 4 – experimental groups, in which females were intraperitoneally administered with glufimet at a dose of 28.7 mg / kg and RSPU260 at a dose of 25 mg / kg once a day for 14 days after cessation of alcohol solution consumption; group 5 – a group of animals receiving a reference listed drug mildronate at a dose of 50 mg / kg according to a regimen similar to that of the studied compounds. Changes in microstructural and morphometric parameters of the left ventricular myocardium were assessed using light microscopy.Results. In animals after CAI, the cardiomyocyte volume fraction decreased, while the interstitial and vascular volume fractions increased. Degeneration of cardiomyocytes, such as their wave-like deformation, loss of transverse striation, foci of plasmolysis, and fragmentation of muscle fibers were revealed. In rats treated with glufimet, the structural changes in cardiomyocytes were minimal. Lower vascular plethora was observed; blood vessels were characterized by single stasis and sludge. The cardiomyocyte volume fraction was 9.7% greater than in control animals, while the interstitial and vascular volume fractions were 66.0 and 70.0% smaller, respectively. The animals treated with the RSPU-260 compound had no significant degenerative changes in cardiomyocytes and small vessels similar to the experimental animals injected with glufimet. Mildronate had a less pronounced cardioprotective effect.Conclusion. Administration of new GABA and glutamic acid derivatives to animals with simulated chronic alcohol intoxication leads to improvement of the microstructure in cardiomyocytes compared with control rats. This indicates pronounced cardioprotective effects of the studied neuroactive amino acid derivatives.